DETERMINATION OF THERMAL EFFICIENCY AND COOKING POWER OF PARABOLIC SOLAR CONCENTRATING SYSTEM WITH THERMAL COMPENSATOR FOR DOMESTIC APPLICATIONS - A. B, BANDE; M. M, GARBA; S, ALIYU; B.S, HAMZA; B.S, HAMZA; A, SHEHU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Energy and the environment have a strong relationship. The production and consumption of energy is one of the biggest causes of environmental damage on earth. Therefore, the rapid increase in the level of CO2 and other greenhouse gases are given out during burning fossil fuel rise or unsteady of fuel prices are the main purposes led to a search to more effectively utilize a different sources of renewable energy. To reduce the consequences of greenhouse gases emitted by burning fuel for energy, which course depletion of the ozone layer and global warming. Therefore, the use of solar radiation directly as a source of energy has proved in the past to be less economical and affordable. The paper was aimed at determination of the performance of a parabolic solar concentrating system with a thermal compensator for domestic applications using thermal efficiency and cooking power. The parabolic dish solar collector (PDSC) with a focal point of 6.15 m, aperture area of 5.8 m2 and rim angle (φo) of 45O was designed and constructed for the determination of the variables. The PDSC was made of stainless steel reflector sheet in such a way that both the manufacturing and assembly method do not require complicated skilled techniques and cost. Since the PDSC is for high temperature steam generation, hot water and cooking application. A finite element stress test analysis was conducted to determine the thermal efficiency and cooking power of the system under various weather conditions. A simple manual solar tracking mechanism was employed, and the results of the system performance were also reported. The efficiency according to the finding depends on the optical properties of the materials involved, the geometry of the collector, and the various imperfections arising from the construction of the collector. The thermal efficiency and cooking power of the system were determined and obtained to be 54.4% and 543.1W respectively.